School Administrator Competencies Affecting School Personnel Management In Vajira Burapha Consortium, Secondary Educational Service Area Office Bangkok 2 - Phoyai, Nattamon; Noymanee, Niwat; Saneechai, Atsavin (Journal of Education Studies, Chulalongkorn University, 2024)
The purposes of research were to study: 1) the school administrator competencies in Vajira Burapha Consortium, 2) the school personnel management in Vajira Burapha Consortium, 3) the relationship between the school administrator competencies and the school personnel management in Vajira Burapha Consortium and 4) the school administrator competencies affecting the school personnel management in Vajira Burapha Consortium. The samples were 301 teachers in Vajira Burapha Consortium by stratified random sampling. The research instrument was a questionnaire for ideas regarding the school administrator competencies and school personnel management in Vajira Burapha Consortium, with IOC score between .60-1.00 and a reliability of .997. Data were analyzed by mean (M), standard deviation (SD), Pearson's product moment correlation coefficient, and Multiple Regression Analysis. The results of the research were as follows. 1) The school administrator competencies in Vajira Burapha Consortium had score at a high level. (M = 4.44,SD = .61), 2) The school personnel management in Vajira Burapha Consortium had score at the highest level, (M = 4.53, SD = .63), 3) The relationship between the school administrator competencies and the school personnel management in Vajira Burapha Consortium was positive at the highest level of significance (.01), and 4) The prediction equation in form of raw scores was: y =.337+.197(X1)+.388(X6)+.191(X8), and in form of standard scores was: Zy = .421(X6)+.206(X1)+.199(X8).